Mathematical modelling of the sintering process of iron-based metal-glass materials - Jabbarov, T.G.; Dyshin, O.A.; Babanli, M.B.; Abbasov, I.I. (Успехи физики металлов, 2019)
Based on the study of the mechanisms of diffuse coalescence and coagulation, we review mathematical methods of description and construction of models for sintering process of the metal–ceramic materials. These models are represented by a set of nonlinear differential equations including bulk, grain-boundary, and surface diffusion coefficients, and correspond to a sequence of the temperature stage levels increasing with a certain rate and having different durations. By adjusting the levels, rates and durations of temperature regimes, technical parameters. На основі дослідження механізмів дифузійної коалесценції та коаґуляції оглядаються математичні методи опису та побудови моделів процесу спікання металокерамічних матеріалів. Ці моделі представлено системою нелінійних диференційних рівнянь, що включають коефіцієнти об’ємної, зерномежової та поверхневої дифузії, а також відповідають послідовності стадійних рівнів температури, зростаючих із певною швидкістю та що мають різні тривалості. На основе исследования механизмов диффузионной коалесценции и коагуляции обозреваются математические методы описания и построения моделей процесса спекания металлокерамических материалов. Эти модели представлены системой нелинейных дифференциальных уравнений, включающих коэффициенты объёмной, зернограничной и поверхностной диффузии, а также соответствуют последовательности стадийных уровней температуры, возрастающих с определённой скоростью и имеющих разные продолжительности.